2020
DOI: 10.1039/d0sc00167h
|View full text |Cite
|
Sign up to set email alerts
|

Systematic exploration of different E3 ubiquitin ligases: an approach towards potent and selective CDK6 degraders

Abstract: Cyclin-dependent kinase 6 (CDK6) is an important regulator of the cell cycle. Together with CDK4, it phosphorylates and inactivates retinoblastoma (Rb) protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
128
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 77 publications
(113 reference statements)
1
128
0
Order By: Relevance
“…Recently, an increasing number of publications have emerged where the physical properties of PROTACs are accounted for in their design, or in the rationalisation of their efficacy [121][122][123][124]. Mares et al [125], developed a potent cIAP-recruiting PROTAC (82) for the degradation of RIPK2 containing a PEG linker (pDC 50 = 9.4 in THP-1 monocytes, Figure 17).…”
Section: Deg S _mentioning
confidence: 99%
“…Recently, an increasing number of publications have emerged where the physical properties of PROTACs are accounted for in their design, or in the rationalisation of their efficacy [121][122][123][124]. Mares et al [125], developed a potent cIAP-recruiting PROTAC (82) for the degradation of RIPK2 containing a PEG linker (pDC 50 = 9.4 in THP-1 monocytes, Figure 17).…”
Section: Deg S _mentioning
confidence: 99%
“…The authors compared BSJ‐03‐123 with their best compound and observed that, still in MM.1S cells, a recovering of CDK6 levels began after 24 h with BSJ‐03‐123, whereas CST651 and CST620 induced a persistent degradation of CDK6 even after 96 h. These compounds also showed very efficient degradation of this kinase in a broad range of different human and murine cancer cells. Moreover, after a washout step, BSJ‐03‐123 kept CDK6 protein levels below 50% for a maximum of 6 h while the two VHL compounds induced low and stable levels of CDK6 for up to 72 h. [ 100 ] This study confirmed that a CRBN‐based PROTAC is not the only way forward to access efficient degraders. Moreover, whereas the nature of the linker has one more time demonstrated a critical effect on the efficacy and selectivity of the PROTACs, the structure of the E3 UL recruiter could also play an important role in these fields.…”
Section: Serine‐threonine Kinases (Stks) Degradersmentioning
confidence: 53%
“…Thus, their inhibition could offer new ways to treat inflammatory or autoimmune diseases. Recently, several STKs were targeted using the PROTAC technology: the interleukin‐1 receptor‐associated kinase 4 (IRAK4), [ 94 ] the serum and glucocorticoid‐induced protein kinase 3 (SGK3), [ 95 ] the polo‐like kinase 1 (PLK1), [ 96 ] several members of the CDK family, [ 97–102 ] and the B isoform of the rapidly accelerated fribrosarcoma (BRAF). [ 103 ]…”
Section: Serine‐threonine Kinases (Stks) Degradersmentioning
confidence: 99%
See 2 more Smart Citations